The Impact Assessment of the VAT reduction in Tourism Sector - Cela, Griselda (European Scientific Journal, ESJ, 2018)
As a part of measures to support tourism sector as one of the government’s strategic priorities, the Albanian government reduced the tourism value added tax (VAT). The main purpose of this article is to analyze the effects of reducing the VAT for Tourism from 20% to 6%. In order to evaluate the impact and benefit of the introduction of the VAT rate reduction in an informed manner and determine whether the objectives of the initiative have been met, the following questions are considered: • Did the reduction in the VAT rate result in lower consumer prices in the impacted categories? • Has there been an increase in tourist numbers as a result of the VAT rate reduction and what has been the impact on revenue? • Has there been an increase in demand / activity in the tourism industry as a result of the VAT rate reduction? • Has there been an increase in employment in the tourism industry as a result of the VAT rate reduction? The assessment framework enables an indicative assessment of the VAT rate cut’s impact through consideration of the key questions referred to previously. The term “indicative assessment” is used owing to the data challenges around aligning various data sets, data lags and the limited time since the cut came into effect. Clearly the question of whether a specific input or policy measure, such as the VAT decrease, has contributed strongly to, or in effect led to, an increase in tourism activity or employment within tourism sector.